PERANCANGAN VIDEO EXPLAINER BERBASIS ANIMASI TENTANG PEDOMAN NON-FUNGIBLE TOKEN BAGI SENIMAN INDONESIA - Calvin Pandapotan Limbong; Mahimma Romadhona; Diana Aqidatun Nisa (JURNAL IMAJINASI, 2023)
Non-Fungible Tokens are ownership of digital assets that are traded like physical assets without worrying about being duplicated or even replicated. One of the drivers of this is the sale of works by Artist Mike Winkelmann or commonly known as Beeple in early 2021 at Christie's Auctions. Many people are starting to look at digital works in the form of Non- Fungible Tokens for several reasons, Non-Fungible Token digital assets are recognized for their security because Non-Fungible Token works are stored in the blockchain. In Designing an Animation-Based Explainer Video About Guidelines for Non-Fungible Tokens for Indonesian Artists as an effort to introduce the world of Non-Fungible Tokens for Indonesian Artists. Explainer Video is an effective way to provide information resources and learning tools to the target group in a very short time. Explainer Videos are usually one to three minutes long. Animation-based Explainer videos can help users more easily understand the contents of the guidelines contained in Non-Fungible Tokens.